2017
DOI: 10.20853/31-3-1064
|View full text |Cite
|
Sign up to set email alerts
|

Accounting students’ profile versus academic performance: A five-year analysis

Abstract: The purpose of the study was to explore first-year accounting students' profile (N= 3075) in terms of academic performance over a period of five years (2010)(2011)(2012)(2013)(2014) at a South African university.The objectives were to determine the impact of students' profile (age, gender, race) and the students' pre-university knowledge brought to lectures (language, subject choice, whether Accounting was a Grade 12 subject) on academic performance. A quantitative research method was used. The study concluded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 18 publications
(20 reference statements)
3
32
2
Order By: Relevance
“…There was a contradiction in the attribution of the teachers to lack of prior knowledge in accounting as the primary cause of students' failure. Although various studies (Papageorgiou, 2017;Al-Mutairi, 2011;Alanzi, 2015;Marinaccio, 2017;Nayebzadeh, Aldin, & Heirany, 2011;Arquero, Byrne, Flood & Gonzales, 2009) conducted around the world proved the importance of prior knowledge, the current study found it not significant to either success or failure of the student in accounting subject. There was no strong reference for failure to teacher-factors such as qualifications and inappropriate teaching methodology.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…There was a contradiction in the attribution of the teachers to lack of prior knowledge in accounting as the primary cause of students' failure. Although various studies (Papageorgiou, 2017;Al-Mutairi, 2011;Alanzi, 2015;Marinaccio, 2017;Nayebzadeh, Aldin, & Heirany, 2011;Arquero, Byrne, Flood & Gonzales, 2009) conducted around the world proved the importance of prior knowledge, the current study found it not significant to either success or failure of the student in accounting subject. There was no strong reference for failure to teacher-factors such as qualifications and inappropriate teaching methodology.…”
Section: Discussioncontrasting
confidence: 77%
“…Taking the different studies that depicted on the importance of the previous knowledge in the study of accounting (Papageorgiou, 2017;Al-Mutairi, 2011;Alanzi, 2015;Marinaccio, 2017;Nayebzadeh, Aldin, & Heirany, 2011;Arquero, Byrne, Flood & Gonzales, 2009), the results of the current study show that students have sufficient background of the subject. Thus, it may not be a factor for failure.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Accounting lecturers and curriculum developers confirm that previous research has shown that those scholars, registered for the Accounting programme at universities, who obtained higher Mathematics' marks in Grade 12 outperform their peers comparing to scholars with lower Mathematic marks (Baard et al 2010). In addition, the marks obtained for English and, at some universities the marks for, Accounting in the final NSC examination are assumed to be a realistic predictor of students' academic performance registered for a degree in Accounting (Műller et al 2007;Baard et al 2010;Papageorgiou 2017; Du Plessis, Műller and Prinsloo 2005).…”
Section: Literature Reviewsupporting
confidence: 62%
“…Factors that influence the academic performance of students, that may prevent students from graduating or extend their degree with a year or longer, have attracted the attention of many researchers; factors such as students' age, gender, attitude, extended curriculum, personality, diversity, transition from secondary to tertiary education and prior academic achievement (Duff 2004;Bergin 2001;Chansarkar and Michaeloudis 2001;Lubbe 2017;Papageorgiou and Halabi 2014;Van Rensburg, Penn and Haiden 1998;Woollacott, Snell and Laher 2013;Duff and Mladenovic 2015;Papageorgiou 2017;Papageorgiou and Callaghan 2018;Steenkamp, Baard and Frick 2009). For some students who enter higher education, career and educational ambitions, individual benefits and quality of learning are the main drivers (Samsuddin, Khairani, Wahid and Sata 2015;Biggs 2003) to academic success.…”
Section: Introductionmentioning
confidence: 99%